Réponses

2013-12-04T14:16:59+01:00
A) (3x+1)²
= 9x²+6x+1

b) (-x+7)²
= x²-14x+49

c) (9-5x)(9+5x)
= 81+45x-45x-25x²
= -25x²+81
excuser moi je me suis trompée ses (7-x)²
pour la questions c
c) (7-x)²
= 49 - 2x + x²
= x² -2x +49

voilà :)
merci :)
La réponse de miloudu5 n'est pas correcte : (-x+7)²
= x²-14x+49
2013-12-04T14:21:00+01:00
A) (3x+1)^2
9x^2+6x+1

identité remarquable

b) (-x+7)^2
x^2-14x+49

identité remarquable

c) (9-5x)(9+5x)
= 81+45x-45x-25x^2
= -
25x^2+81

identité remarquable
excuser moi je me suis trompée ses (7-x)²
pour la questions c
c) (7-x)²
= 49 - 2x + x²
= x² -2x +49